2017
DOI: 10.1158/0008-5472.can-17-2194
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Haplotype Alters Mammary Cancer Tumorigenicity and Metastasis in an Oncogenic Driver–Dependent Manner

Abstract: Using a novel mouse model, a mitochondrial-nuclear exchange model termed MNX, we tested the hypothesis that inherited mitochondrial haplotypes alter primary tumor latency and metastatic efficiency. Male FVB/N-Tg(MMTVneu)202Mul/J (Her2) transgenic mice were bred to female MNX mice having FVB/NJ nuclear DNA with either FVB/NJ, C57BL/6J, or BALB/cJ mtDNA. Pups receiving the C57BL/6J or BALB/cJ mitochondrial genome (i.e., females crossed with Her2 males) showed significantly (P < 0.001) longer tumor latency (262 v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 56 publications
5
25
0
Order By: Relevance
“…In RA, radiographic erosions were significantly associated with the JT haplogroup [62] and, in early RA, an association was reported between erosions and increased intraarticular blood flow [63]. The mtDNA haplogroup has also been related to cancer risk [64][65][66].…”
Section: Pathological Angiogenesis Is a Feature Of Many Oxphos Disordersmentioning
confidence: 99%
“…In RA, radiographic erosions were significantly associated with the JT haplogroup [62] and, in early RA, an association was reported between erosions and increased intraarticular blood flow [63]. The mtDNA haplogroup has also been related to cancer risk [64][65][66].…”
Section: Pathological Angiogenesis Is a Feature Of Many Oxphos Disordersmentioning
confidence: 99%
“…Crossing nDNA-matched mice with female MNX mice allows segregation of mtDNA influence from nuclear genes. Using this model, we demonstrated that the mitochondrial genome alters tumor progression and metastasis [62,63,59] in the PyMT model nearly identical to what was observed in the wild-type mouse crosses. Furthermore, crossing MNX mice with mice over-expressing the HER2/Neu oncogene, we observed driver-dependent alterations in tumorigenesis and metastasis [62].…”
Section: Mitochondrial Dna and Metastasismentioning
confidence: 84%
“…Using this model, we demonstrated that the mitochondrial genome alters tumor progression and metastasis [62,63,59] in the PyMT model nearly identical to what was observed in the wild-type mouse crosses. Furthermore, crossing MNX mice with mice over-expressing the HER2/Neu oncogene, we observed driver-dependent alterations in tumorigenesis and metastasis [62]. While not the focus of this review per se , MNX mice have uncovered existence of mtDNA modifier loci in cardiovascular disease [61], atherosclerosis [61,64], and obesity [63], strongly supporting a closer look at mitochondrial quantitative trait loci [65,66].…”
Section: Mitochondrial Dna and Metastasismentioning
confidence: 84%
See 1 more Smart Citation
“…MNX mice contain nuclear DNA contribution from one strain of mice and mitochondrial DNA contribution from another strain. We previously showed that mitochondrial backgrounds selectively affect tumor latency [37,39], metastasis [37,39], obesity [38], and cardiovascular disease [15]. Additionally, mitochondrial genomic backgrounds also affect nuclear DNA methylation [38], histone marks (J. McGuire and D.R Welch, in preparation) and gene expression.…”
Section: Introductionmentioning
confidence: 99%